Monitoramento limnológico em canais das bacias hidrográficas do rio Pirapozinho e do córrego Limoeiro / Marcia Aparecida da Silva - Silva, Márcia Aparecida da [UNESP] (2014)
The main purpose of this work was the limnological monitoring to verify the water quality of the Limoeiro stream water in the city of Presidente Prudente - SP, and the Pirapozinho River located in the city of Pirapozinho - SP from 2006 to 2013. In this study, I analyzed the behavior of these water bodies when they no longer received domestic sewage without treatment from the referred cities since the construction of wastewater treatment plants. The choice of parameters monitored was made based on the criteria of cost, time and labor. Similarly, I selected the sections in the channels of the river basins in order to coincide with those of my routine work. The methodology used was based on work instructions found on Standard Methods For Examination of Water and Wastewater 22nd Edition, 2012. The results obtained during the studies pointed to an improvement in both sections and the records of COD, BOD and DO were the variables that most significantly recovered in these water bodies. Based on the results, from 2008 onwards the streams that did not receive urban sewage showed significant recovery of its purity, with their water less polluted and their quality standards within their environmental framework classes